Microstructure and mechanical behavior of lithium slag-quartz sand cemented backfill: influence of particle gradation and content - Liu, Rongxi; Wang, Lei; Xu, Sidong; Zhu, Daopei; Zuo, Liping (Frontiers in Materials, 2025)
To achieve the sustainable development of industrial solid waste resource utilization and mining environmental remediation, this study investigates the mechanical properties and microstructure of cemented backfill (LQCB) prepared from lithium slag (LS) and quartz sand (QS) under different mix proportions. Through uniaxial compressive strength (UCS) tests, stress-strain analysis, and scanning electron microscopy (SEM) observation, the effects of QS content (10%–50%), particle size (1–8 mm), and cement-to-liquid ratio (C/Ls = 1:2, 1:4, 1:6) were systematically evaluated. The results show that when the QS content is 30%, particle size is 1–2 mm, and C/Ls is 1:2, the LQCB achieves optimal strength and compactness, with a UCS of 0.77 MPa and a minimum crack width of 15 μm. A higher QS content (≥50%) or excessively coarse particles increase porosity and weaken the interfacial transition zone, leading to a maximum UCS reduction of 63%. However, when the QS content is maintained at 30% with a particle size of 4–8 mm, the LQCB exhibits a maximum UCS of 1.07 MPa. SEM analysis confirms that the uniform distribution of hydration products (C-S-H and AFt) improves the microstructural integrity, while excessive QS results in widened cracks (up to 94.7 μm) and strength loss. The findings provide valuable guidance for optimizing the LQCB mix proportion, enhancing its performance, and promoting the reuse of solid waste.